Prevalence and Pattern of Zygomatic Complex Fracture in a Tertiary Care Hospital of Central Nepal - Dhungel, Safal; Roy, Prabhash; Thapa, Nisha; Devkota, Kriti (Journal of College of Medical Sciences-Nepal, 2024)
Background Zygomatic complex fracture is one of the commonest fractures of face leading to facial asymmetry. Various classification systems describing the pattern have been reported. The aim of this study was to determine the prevalence and pattern of Zygomatic maxillary complex fracture in tertiary centre hospital of Nepal based on two different classifications. Methods A prospective observational study was conducted on College of Medical Sciences, Teaching Hospital, Chitwan from September 2021 to August 2023 with all cases of facial injuries. Computed Tomography scan of the cases were considered and 371 cases with Zygomatic maxillary complex fracture were studied. Apart from the demographic data, Knight and North classification and Zing Classification of the fractures were recorded. The data was tabulated and analysed using SPSS 20. Results Zygomatic maxillary complex fracture was prevalent in third decayed of life with mean age of 28.45 years. Male (286) were more affected. Road traffic accident is primary cause of the fracture in our study. Type III fracture (31.35%) on Knights classification is commonest pattern followed by type VI (18.65%), type V (13.99%) and type II (14.77%). On Zing classification type B (53.89%) of Zing classifications is more prevalent followed by type C (19.69%) and type A2 (17.36%). Conclusions The study describes the demographic distribution, aetiology and pattern of Zygomatic complex fracture in a tertiary hospital.